Antidepressant treatment-related brain activity changes in remitted major depressive disorder. (April 2023) - Yang, Xiao; Kumar, Poornima; Wang, Min; Zhao, Liansheng; Du, Yue; Zhang, Belinda Y.; Qi, Shile; Sui, Jing; Li, Tao; Ma, Xiaohong
Highlights: Graph theory was used to map the degree of intrinsic brain connectivity. Functional connectivity changes of remitted depression were identified. Degree centrality of DMPFC may be a neuroimaging biomarker for depression. Abstract: Recent evidence has shown that some brain regions are core hubs and play a key role in the treatment of depression. Twenty-five unmedicated patients with major depressive disorder (MDD) were included, and telephone follow-up was performed at 8, 24, and 48 weeks after enrollment. After reaching clinical remission, they were scheduled for a second magnetic resonance imaging scan and clinical evaluation. Thirty-one healthy controls were also investigated. The intrinsic functional connectivity (degree centrality) of each participant was mapped using a computationally efficient approach. Then, functional connectivity of patients was calculated between the identified regions of interest by degree centrality analysis and every voxel. Later, linear regression analysis was used to identify potential variables predictive of an improvement in disease severity. The prominent hubs identified by degree centrality analysis included the cerebellum, inferior temporal gyrus, lingual gyrus, dorsal medial prefrontal cortex (DMPFC), and dorsal lateral prefrontal cortex. We also found that the increased degree centrality of DMPFC was associated with improvement in depressive symptoms. The brain activity associated with antidepressant effects, especially brain connectivity changes in the left DMPFC, can potentially be used to monitor treatment response and predict treatment outcomes.